Analisis Persaingan Bisnis Syariah Menggunakan Pendekatan Porter Five Forcess Pada Kspps Hanada Quwais Purwokerto - Aprilia Tri Wahyuni; Iska Inayatun Aulia; Sheila Prasetiowat; Yoiz Shofwa Shafran (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study investigates the competitive dynamics of the Islamic business sector at KSPPS Hanada Quwais Purwokerto using the Porter Five Forces framework and an Islamic strategic management perspective. The research employs a descriptive qualitative methodology based on literature analysis, interviews, and observation. The research indicates that there are few hazards from substitute items, that suppliers and customers have a fair degree of bargaining power, that entry barriers are high, and that competition is intense. The combination of sharia values, supply chain management, differentiation tactics, product innovation and digitization, and a strong dedication to sustainability and social responsibility all contribute to KSPPS Hanada Quwais's competitive edge. These results highlight the significance of implementing sharia principles in all facets of business operations and offer strategic insights for Islamic cooperatives to preserve and improve their position in a cutthroat market.